2019
DOI: 10.1016/j.heliyon.2019.e01390
|View full text |Cite|
|
Sign up to set email alerts
|

Myanmar's human resources for health: current situation and its challenges

Abstract: Background Human resources for health (HRH) are the cornerstone of health systems, enabling the improvement of health service coverage. The systematic fortification of healthcare in Myanmar has accelerated since a new ruling party took office. Since 2006, Myanmar has been listed as one of the 57 crisis countries facing critical health workforce shortages. Therefore, this study aimed to assess the current situation of HRH in the public health sector where major healthcare services are provided to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 10 publications
2
57
0
1
Order By: Relevance
“…The major reason for late diagnosis and treatment in Myanmar was the lack of trained health staff for managing NCDs at primary health facilities [24]. Overall there is a shortage of doctors with Myanmar's human resources for health in 2017 reporting that 13 out of 15 states and regions were below the WHO recommended minimum number of 1 per 1000 population for medical doctor [25]. Also, a study assessing the implementation of NCD care at primary health facilities of Myanmar reported a lack of infrastructure and drugs for managing NCD patients at primary health facilities [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major reason for late diagnosis and treatment in Myanmar was the lack of trained health staff for managing NCDs at primary health facilities [24]. Overall there is a shortage of doctors with Myanmar's human resources for health in 2017 reporting that 13 out of 15 states and regions were below the WHO recommended minimum number of 1 per 1000 population for medical doctor [25]. Also, a study assessing the implementation of NCD care at primary health facilities of Myanmar reported a lack of infrastructure and drugs for managing NCD patients at primary health facilities [24].…”
Section: Discussionmentioning
confidence: 99%
“…The piloted "WHO Package of Essential Noncommunicable Disease Interventions (WHO PEN)" for primary care has to be universalized throughout the country. The trained health workforce has to be increased as the country has 1.3 health workers per 1000 population, compared with WHO's recommended threshold of 4.45 per 1000 population required for Universal Health Coverage [25]. The primary health centers need to be strengthened and community health workers have to be trained to identify, diagnose, and treat common NCDs in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Although many researchers have indicated that HRH availability has improved in some countries, out-of-balance, insufficient, and limited HRH availability persists in many other countries. Therefore, many countries still need to develop a long-term HRH plan [1][2][3][4][5][6][7][8] . Narasimhan (2004) [9] claimed that the quantity and distribution of HRH directly influence the quality of medical services and the long-term development of the medical system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These experiences have been shown to decrease worker morale and productivity, which can lead to increased absenteeism, burnout, and attrition [2][3][4]. WPV and its effect on health workers place more strain on an already challenged human resource sphere in Myanmar [5]. The prevalence of WPV against healthcare groups around the world has been previously studied, revealing a wide range of reported experiences [6,7].…”
Section: Introductionmentioning
confidence: 99%